Managing External Pressures in the Maritime Industry : Strategic responses to climate-induced management pressures - Mäkinen, Juho (My University, 2022)
The climate crisis is a tumultuous topic that has gained global traction and interest among political and business leaders. From an international business perspective, the issue is perpetuated by the infinite need for economic growth and the resources with which said growth is produced. Resource-intensive growth results in ever-increasing carbon emissions, which in turn exacerbate the climate crisis. The issue is wicked and complex to the extent that individual organizations are otiose in attempting to fix it. Thus, mitigating the effects of the climate crisis with collective action is imperative. The maritime industry fuels world trade and is thus a major contributor to increased carbon emissions. Maritime operators strive for efficiency as industry profit margins are low, which predisposes most businesses to desist from sustainable reform. Hence, there is a dire need for sustainable value promulgation research in the industry. By combining resource dependence theory and institutional theory, Oliver (1991) theorized a framework for strategic responses to institutional processes. This thesis studies resource dependence theory, the maritime institutional environment, and Oliver’s (1991) framework to identify how managers confront external sustainability pressures to ensure their company’s survival in the maritime industry. This amalgamation of theory is juxtaposed against interviews with maritime researchers and experts to produce insights on how external factors shape organizational management decisions. The research design thus addresses a previously identified research gap introduced by scholars of maritime sustainability. Antecedents, namely cause, constituents, content, control and context, affect an organization’s choice of strategic management responses in face of external pressures. Strategic responses include acquiescence, compromise, avoidance, defiance and manipulation. A key finding in this thesis is that the scope of strategic responses to external pressures is not necessarily limited to resistance, as hypothesized by Oliver (1991). Proactive conformance is suggested to be a sixth viable strategic option that may increase profit margins and augment the size of the overall market for sustainable business. Findings also suggest that the financial limitations that are known to hinder the industry’s green transition can be circumvented through differentiation and specialization. Moreover, shaping high sustainability performance markets and organizations within them could be an efficient first step for those entities looking to promulgate sustainable change. Further research is required to confirm and explore how proactive conformance augments the toolbox of discretionary action available to organizations in the face of external pressures.

Ilmastokriisi on mittava maailmanlaajuinen ongelma, jota on pitkään puitu kansainvälisessä keskustelussa. Kansainvälisen liiketoiminnan näkökulmasta ongelma kiteytyy kasvukeskeiseen talousajatteluun ja erityisesti resurssipohjaiseen kasvuun. Resurssien kulutus kasvattaa hiilidioksidipäästöjä, mikä syventää ekologista kriisiä entisestään. Koska maailmantalous perustuu monimutkaiseen yritysverkostoon, ei ilmastokriisiä voi ratkoa ilman monitahoista yhteistyötä. Meriteollisuus on keskeinen osa maailmantaloutta ja samalla suuri ilmastopäästöjen aiheuttaja. Koska ala on kilpailtu ja katteet jäävät useilla yrityksillä pieniksi, monet meriteollisuuden yritykset keskittyvät taloudelliseen tehokkuuteen, jolloin kestävä kehitys jää tausta-ajatukseksi. Siksi on mielekästä tutkia kestävän liiketoiminnan edistämistä meriteollisuudessa ja kestävän kehityksen hyötyjen laajamittaista tunnustamista yritysverkostoissa. Oliver (1991) yhdisti resurssipohjaisen ja institutionaalisen talousajattelun piirteet viitekehykseksi, jonka avulla voidaan tulkita liiketoimintaympäristöjä ja ennakoida organisaatioiden strategisia valintoja niiden kohdatessa ulkoisia paineita. Tällä tutkimuksella pyritään selvittämään millä tavoin johtajat käsittelevät ulkoisia kestävyyspaineita pärjätäkseen meriteollisuuden kilpaillussa toimintaympäristössä. Tutkimus yhdistää resurssipohjaisen teorian meriteollisuuden liiketoimintaympäristöön Oliverin (1991) viitekehyksen avulla. Teoriaa peilataan alan asiantuntijoiden haastatteluvastauksiin ja näkemykset avaavat ulkoisten tekijöiden todennäköisiä vaikutuksia organisaatioiden päätöksentekoon. Tämä tutkimusmalli täyttää aiempien tutkimusten jättämiä aukkoja meriteollisuuden kestävän kehityksen tutkimuksessa. Tulosten valossa Oliverin (1991) nimeämät ennakointitekijät näyttävät vaikuttavan johtajien tekemiin päätöksiin. Ennakointitekijöitä ovat paineiden alkuperä (eng. cause), sidosryhmät (contituents), sisältö (content), hallinta (control) ja asiayhteys (context). Strategisia vaihtoehtoja ovat Oliverin mukaan myöntyminen (acquiescence), kompromissit (compromise), välttely (avoidance), uhmaaminen (defiance) ja manipulaatio (manipulation). Tässä tutkimuksessa kuitenkin havaitaan, että organisaatioiden ei aina tarvitse vastustaa ulkoisia paineita, toisin kuin Oliver (1991) väittää. Tulosten perusteella paineisiin voi myös mukautua proaktiivisesti. Proaktiivisuuden havaitaan kehittävän katetuottavuutta ja kasvattavan kestävän liiketoiminnan markkinaa. Tulosten perusteella ehdotetaan, että meriteollisuuden taloudellisia haasteita voidaan lieventää erottautumalla ja erikoistumalla – tämä luo myös edellytyksiä kestävän liiketoiminnan harppaukselle (green transition). Kestävän liiketoiminnan edistäminen tulisi aloittaa maista, joissa kestävä kehitys on jo valmiiksi pitkällä. Näissä maissa on lähtökohtaisesti suurempi institutionaalinen paine mukautua kestävyysvaatimuksiin. Tulevien tutkimusten tulisi keskittyä proaktiivisen mukautumisen tutkimiseen ja tässä tutkimuksessa esitetyn uudistetun teorian vahvistamiseen ja soveltamiseen eri tutkimusasetelmissa.
Keywords: Sustainability management, resource dependence theory, institutional theory, maritime sustainability, value networks, promulgating values, corporate activism